2020
DOI: 10.1016/s1470-2045(19)30797-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signatures related to the obesity paradox in patients with clear cell renal cell carcinoma: a cohort study

Abstract: Data sharingNovartis is committed to sharing access to patient-level data and supporting clinical documents from eligible studies with qualified external researchers. These requests are reviewed and approved by an independent review panel on the basis of scientific merit. All data provided are anonymized to respect the privacy of patients who have participated in the trial in line with applicable laws and regulations. This trial data availability is according to the criteria and process described on www.clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 47 publications
6
132
0
Order By: Relevance
“…The study by Hakimi confirmed a strong correlation between BMI and OS of the assessed cohort but noted a stronger correlation in the sunitinib-treated group than the pazopanib group [66]. This trend was also reported in the subsequent study by Sanchez and team [13], confirming a stronger association of BMI with sunitinib in metastatic RCC patients. Previously, a combination of atezolizumab and bevacizumab was shown to result in better clinical benefit than sunitinib in RCC patients [67].…”
Section: Targeted/immunotherapy-treated Rcc Patientssupporting
confidence: 67%
See 2 more Smart Citations
“…The study by Hakimi confirmed a strong correlation between BMI and OS of the assessed cohort but noted a stronger correlation in the sunitinib-treated group than the pazopanib group [66]. This trend was also reported in the subsequent study by Sanchez and team [13], confirming a stronger association of BMI with sunitinib in metastatic RCC patients. Previously, a combination of atezolizumab and bevacizumab was shown to result in better clinical benefit than sunitinib in RCC patients [67].…”
Section: Targeted/immunotherapy-treated Rcc Patientssupporting
confidence: 67%
“…Recently, Sanchez and colleagues [13] exclusively studied transcriptomic signatures related to the obesity paradox in both the tumor tissue and PAT of ccRCC patients who underwent immunotherapy or surgical intervention. In general, compared to normal BMI patients, tumors from obese patients overexpressed wound healing (TGF-β, epithelial-mesenchymal transition, hedgehog, and notch), hypoxia, and angiogenesis (VEGF and DOI: 10.1159/000510245 VEGF receptor 2) signaling pathways, along with the metabolic pathways, involved in adipogenesis, glycolysis, and fatty acid metabolism.…”
Section: Tumor and Peritumoral Fat Microenvironment In Normal Bmi Vermentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that obesity has been recognized as a major underlying factor in the pathogenesis of serious OS-related health problems, such as hyperlipidemia [7], insulin resistance [8], hypertension [9], type 2 diabetes [10], cardiovascular diseases [7] and certain types of cancer [11]. Overweight/obesity has been shown to adversely affect the condition of the oral cavity, including salivary gland function [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Interestingly, obesity also provides an improved survival. 4 The majority of RCC subtypes are classified as clear cell renal cell carcinoma (ccRCC), which account for almost 70-75% of all RCCs. 5 Cancer-specific survival rate at 5 years for ccRCC patients is 68.9% and ccRCC has a poorer prognosis compared with other RCC such as papillary and chromophobe RCC (p < 0.001).…”
Section: Introductionmentioning
confidence: 99%